Pengolahan Sampah dengan Alat Pembakar Sampah Tanpa Asap (APSTA) di Desa Ganeas Kabupaten Sumedang - Etih Hartati; Waluyo; Bali Widodo (UNISBA Press, 2024)
Abstract. One of the tridarma of higher education is community service. This article presents community service activities in Ganeas Village, Ganeas District, Sumedang Regency, West Java Province. The activities carried out in the form of counseling for the people of Ganeas Village were attended by mothers and fathers. The counseling material is in the form of an explanation of what waste is, types of waste, waste management objectives, waste reduction, handling, waste processing, smokeless waste burner (APSTA). The method of designing a smokeless waste burning device uses the assembly method of a smokeless waste burner. Tool assembly is putting together all the components that have been prepared and measured according to calculations so that they become a single unit of equipment that is ready to be operated. The use of APSTA is the right solution because with this tool there is no smoke that pollutes the environment. APSTA consists of components of a waste burning furnace equipped with a door to enter the garbage and ash collection room, motor, chimney, blower, water storage tank. The counseling was attended by about 45 women and 10 men. The results of this activity are the availability of APSTA technology, increasing community knowledge about APSTA and handling waste in Ganeas Village. Abstrak. Salah satu tridarma pergurian tinggi adalah pengabdian kepada masyarakat. Artikel ini menyajikan kegiatan pengabdian kepada masyarakat, di Desa Ganeas Kecamatan Ganeas, Kabupaten Sumedang, Provinsi Jawa Barat. Kegiatan yang dilakukan berupa penyuluhan bagi masyarakat Desa Ganeas yang dihadiri oleh ibu-ibu dan bapak-bapak. Adapun materi penyuluhan berupa penjelasan tentang apa sampah itu, jenisnya sampah, tujuan pengelolaan sampah, pengurangan, penanganan, pengolahan sampah, alat pembakar sampah tanpa asap (APSTA). Metode perancangan alat pembakaran sampah tanpa asap menggunakan metode perakitan alat pembakar sampah tanpa asap. Perakitan alat adalah menyatukan seluruh komponen-komponen yang sudah disiapkan dan diukur sesuai perhitungan sehingga menjadi satu kesatuan alat yang siap untuk dioperasikan. Penggunaan APSTA adalah solusi tepat karena dengan alat tersebut tidak ada asap yang mencemari lingkungan. APSTA ini terdiri atas komponen-komponen tungku pembakar sampah yang dilengkapi dengan pintu untuk masuk sampah serta ruang penampung abu, motor, cerobong asap, blower, tangki penampung air. Penyuluhan dihadiri sekitar 45 ibu-ibu dan 10 bapak-bapak. Hasil dari kegiatan ini adalah tersedianya teknologi APSTA, meningkatnya pengetahuan masyarakat tentang APSTA dan tertanganinya sampah di Desa Ganeas.